Characterization of exposure–Clinical Dementia Rating–Sum of Boxes relationship in subjects with early Alzheimer’s disease from the aducanumab Phase 3 trials - Muralidharan, Kumar Kandadi; Kowalski, Kenneth G.; Tong, Xiao; Haeberlein, Samantha Budd; Rajagovindan, Rajasimhan; Nestorov, Ivan (Journal of pharmacokinetics and pharmacodynamics, 2023)
Clinical Dementia Rating–Sum of Boxes (CDR–SB) assessments from two Phase 3 studies (ENGAGE and EMERGE) of aducanumab in subjects with early Alzheimer’s disease (AD) were pooled to develop an exposure–response (ER) model. A linear model in the logit-transformed scaled CDR–SB best characterized the time profile for placebo- and aducanumab-treated subjects, with concentration as the exposure metric. The model allowed delineation of slow (4%), typical (86%), and fast (10%) progressing subpopulations in the data. The estimated drug effect on the disease progression rate was significant, 2.05 L/(g·year), with a 95% confidence interval (1.60, 2.50) that did not include zero. Following an evaluation of a series of ER model forms including differential drug and null effects either between the studies or among the three progression classes, the final ER model with a common (pooled) estimate of the drug effect between the studies and among the three progression classes was considered parsimonious. The final model provides supportive evidence that the two studies demonstrate a common intrinsic pharmacology. None of the identified covariates (Mini-Mental State Examination–BL score and Asian race) were clinically meaningful. Finally, simulations demonstrated that the intrinsic pharmacology remained consistent between the two Phase 3 studies.